Chemical Characterization of Flour Fractions from Five Yam (Dioscorea alata) Cultivars in Indonesia - Lula Nadia; M. Aman Wirakartakusumah; Nuri Andarwulan; Eko Hari Purnomo; Takahiro Noda; Koji Ishiguro (Journal of Engineering and Technological Sciences, 2015)
The purpose of this study was to investigate the influence of particle size on  the  chemical properties  of yam flour  in five  cultivars, yellow/YY, orange/OY, light purple/LPY, purple/PY, and dark purple/DPY. With a mesh sieve, three  flour fractions  were separated according to particle size:  small (128.6-139.7 µm), medium (228.7-257.9 µm), and large (475.4-596.3 µm). The content of moisture (6.81-11.26 %db) and lipids (4.48-9.85 %db) decreased with the increase of particle size, while proteins (4.48-9.85 %db) and carbohydrates (78.12-83.76 %db) were not influenced by particle size. Folin-Ciocalteu reagent and chlorogenic acid were used as standard to investigate the total phenolic compounds  in  the  yam  flour,  and  high-performance liquid chromatography (HPLC) was used to investigate the anthocyanin and carotene contents. It was found that there was no size influence on the content of phenolics (0.27-2.82%db), anthocyanin (2.25-15.27  mg/100g db) in LPY, PY, DPY  or  carotene (23.75-132.12 mg/100g db) in YY, OY. The differences in chemical composition were due to differences in particle size and heat treatment, but may also have been caused by the different composition of the milling process.